Erin Brockovick - Soderbergh, Steven (Quezon City : Magnavision.)
Erin Brockovich is a stirring, funny and unconventional drama based on true events, starring two-time Academy Award nominee Julia Roberts as the twice-divorced mother of three young children who sees an injustice, take on the bad guy and wins. With no money, no job and no prospects on the horizon, Erin Brockovick (roberts) is a woman in tight spot. Following a car accident in which Erin is not at fault, she finds herself even worse off when her attorney fails to land her any kind settlement. With nowhere else to turn, Erin pleads with her attorney Ed Marsy (albert Finney) to hire her at his law firm. It is there, while working that she stumbles upon some medical records placed in real estate files. Confused, she begins to question the connection. She convinces Ed to allow her to investigate, where she discovers a cover-up involving contaminated water in a local community which is causing devastating illnesses among its residents. going door to door, she signs up over 600 plaintiffs, and Erin and Ed, with the help of a major law firm, go on to receive the largest settlement ever paid in a direct-action lawsuit in U.S. history... S333 million. By triumphing over insurmountable odds, she is able to prove herself, and reinvent her life.